2022
DOI: 10.1039/d2cc00167e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polycyclic aminal heterocycles via decarboxylative cyclisation of dipeptide derivatives

Abstract: An oxidative-decarboxylative intramolecular cyclisation of dipeptide derivatives is reported. This transformation is promoted by phenyl iodine (III) diacetate (PIDA) in combination with BF3·OEt2. The reaction gives access to a variety...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The latter can either be oxidized to afford the iminium ion. [78][79][80][81][82][83] The former, serving as one of the few examples of applying such strategies in total synthesis, was applied by Rippel et al 84 in the racemic synthesis of Cernumidine.…”
Section: Aminal Synthesis: Decarboxylative Couplingmentioning
confidence: 99%
“…The latter can either be oxidized to afford the iminium ion. [78][79][80][81][82][83] The former, serving as one of the few examples of applying such strategies in total synthesis, was applied by Rippel et al 84 in the racemic synthesis of Cernumidine.…”
Section: Aminal Synthesis: Decarboxylative Couplingmentioning
confidence: 99%
“…A similar reactivity was also observed by the Waser group in their report of intramolecular cyclisation of dipeptide derivatives. 46 However, for their substrates light input was not required.…”
Section: Reactions Of Acyclic Hirsmentioning
confidence: 99%
“…Recently, we found that visible light excitation of phenyliodine( iii ) dicarboxylate–BF 3 complexes leads to a decarboxylative Ritter amination via carbenium intermediates (Scheme 1b). 6 The strategy is quite unique in a sense that it does not require any photocatalyst to mediate the electron transfers to obtain the charged intermediates. 7 Moreover, it is based on simple commercial reagents, without the need for any sophisticated oxidizing agents.…”
mentioning
confidence: 99%